The pharmacokinetics of midazolam and 1-OH-midazolam during oral premedication in paediatric patients - Bartkowska-Śniatkowska, Alicja; Wiczling, Pawel; Juzwa-Sobieraj, Magdalena; Kałużna, Ewelina; Świątek-Kościelna, Bogna; Bienert, Agnieszka; Borsuk, Agnieszka; Tezyk, Artur; Rosada-Kurasinska, Jowita; Januszkiewicz-Lewandowska, Danuta (Journal of Medical Science, 2016)
Objective. Development of midazolam (MDZ) pharmacokinetic model is pivotal for predicting drug response and determining appropriate dosing in patients who undergo surgical procedures. The aim of this study was to provide population pharmacokinetic analysis describing MDZ and its main metabolite 1-OH-midazolam (1-OH-MDZ) used during oral premedication in surgical paediatric patients. The influence of gender, age,  and body weight on MDZ pharmacokinetics was also investigated.Material and Methods The analyzed data set included 27 patients, aged 1 to 17 years, who received oral midazolam syrup before various surgical procedures. The 1-OH-MDZ concentration was approximated by a proportional relationship to MDZ concentration. Population nonlinear mixed-effect modeling was done using NONMEM 7.2. Non-parametric bootstrap and VPC were conducted to evaluate the adequacy of the model to describe the observations.Results Midazolam pharmacokinetic model was developed to describe the time course of MDZ and 1-OH-MDZ concentrations. High inter-individual variability in volume of central compartment (93%) and clearance (60%) of MDZ w ere observed. The effect of body weight was accounted for by the allometric scaling. Significant differences in MDZ pharmacokinetics due to the age and gender were not found.Conclusions The population MDZ pharmacokinetic model was successfully developed for paediatric patients. Age, gender do not explain inter-individual variation in the pharmacokinetics of MDZ. No effect of maturation was detected.